International relations between Cuba and the Caribbean in the 1990s : challenges and perspectives. - GONZALEZ NUNEZ, Gerardo (1997)
Discusses the gradual re-integration of Cuba into the Caribbean in recent years. Points out that the difficulties Cuba has experienced in establishing stable trade relations with the rest of the Caribbean nations are the result of the close links of the Caribbean nations with the US market. Notes that at a strictly regional level, there are issues that could serve as a basis for broad and mutually beneficial collaboration and the development of a common agenda with regard to issues such as migration, durg trafficking and environmental protection.